THE IMAGE OF AN ETHNIC HERO IN DASTAN STORIES (American Journal of Interdisciplinary Research and Development, 2024)
This article, based on the richest factual material, examines the image of the ethnic hero in the dastan stories, provides judgments regarding his artistic originality, and contains a number of theoretical views on the essence of positive and negative images. It is noted that an important place in the epic is occupied by motives that determine the hero’s virtues, his patriotism, punishment of oppressors, the struggle for justice and truth, and the achievement of life-affirming goals. In addition, an important point is that in the dastan stories the ethnic hero and the image of the horse should be considered as a holistic unity.